Preferensi Konsumen terhadap Beras Berlabel Jaminan Varietas (BBJV) untuk Hipa 8, Ciherang dan Inpari 13 - Indrasari, Siti Dewi; Purwaningsih, Purwaningsih; Apriyati, Erni; Ardhiyanti, Shinta Dewi (Jurnal Penelitian Pertanian Tanaman Pangan, 2016)
The objectives of this research was to study the consumer acceptance to variety assurance rice labelledÂ  (VARL) wihich is produced byÂ  âKopkarlittanâ of Indonesian Center for Rice Research (ICRR). The research was conducted on September to November 2013. The respondents were asked to answer the question in questionaire and assessing the rice and cooked rice presented. The preference assessment was carried out to every rice atributesÂ  such as aroma, color, shape, wholeness, cleaness and general acceptance (like or dislike). The same assessment was also carried out to the cooked rice with different atributes such as aroma, color, translucency, softness, taste and general acceptance. The rice used were Hipa 8 variety which is represent aromatic rice and Ciherang and Inpari 23 represent non aromatic rice. Those rice were produced by âKopkarlittanâ ICRR. As controlled were used non variety assurance labelled rice (NVARL) which were bought from two modern market LM and C in Jakarta. The organoleptic data were analysed by Kruskal-Wallis test and presented in decriptive way. In general the respondentsÂ  stated that VARL products is better than other NVARL product in term of shape, wholeness, cleaness, taste of cooked rice, nutritional and functional quality. Other respondents stated that VARL products is the same with NVARL products in term of color. In general the consumers in Jakarta, Bandung and Yogyakarta statedÂ  thatÂ  there is no preference different based on color, aroma, shape, wholeness and cleaness of aromatic rice sold in LM and C modern market, except general accetance atribute of Hipa 8 variety. The consumers also stated that there is no preference different to Hipa 8 cooked rice based on aroma, color, translucency, softness, taste and general acceptance. But there is preference different of aromatics cooked rice sold in LMÂ  modern market based on color, translucency, softness and taste atributes. In general consumers in Jakarta, Bandung and Yogyakarta stated thatÂ  there is no preference different ofÂ  non aromatic rice and cooked rice sold in LM, C modern market dan Inpari 13 variety.